American pastoral - Roth, Philip 1933-2018 (Vintage Internat., 1998)
An ordinary man finds that his life has been made extraordinary by the catastrophic intrusion of history when, in 1968 his adored daughter plants a bomb that kills a stranger, hurling her father out of the longed-for American pastoral and into the indigenous American berserk.
Keywords: Geschichte; Estados Unidos - Historia - 1961-1969 - Novela; USA; United States -- History -- 1961-1969 -- Fiction; Fiktionale Darstellung; Historical fiction; Novela estadounidense - Siglo XX; Pastoral fiction